1999
DOI: 10.1016/s0924-9338(99)00224-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related clinical differences in obsessive-compulsive disorder

Abstract: The purpose of the present study was to investigate the gender-related differences of clinical features in a sample of obsessive-compulsive (OCD) patients. One hundred and sixty outpatients with a principal diagnosis of obsessive-compulsive disorder (DSM-IV, Y-BOCS = 16) were admitted. Patients were evaluated with a semi-structured interview covering the following areas: socio-demographic data, Axis I diagnoses (DSM-IV), OCD clinical features (age at onset of OC symptoms and disorder, type of onset, life event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
83
3
22

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 15 publications
14
83
3
22
Order By: Relevance
“…6,23,33 On the other hand, several studies found no gender differences regarding major depression comorbidity, which is the most common Axis I disorder in both genders. 21,22,24,25,37,47 In an Italian study, 19 men presented more social phobia, tic disorders, and hypomania episodes. In Brazil, Torresan et al 25 found more posttraumatic stress disorder and tic disorders among men, whereas women presented more simple phobias, eating disorders (anorexia nervosa), as well as more impulse control disorders in general, particularly skin picking and "compulsive" shopping.…”
Section: Phenotypical Studiesmentioning
confidence: 97%
See 4 more Smart Citations
“…6,23,33 On the other hand, several studies found no gender differences regarding major depression comorbidity, which is the most common Axis I disorder in both genders. 21,22,24,25,37,47 In an Italian study, 19 men presented more social phobia, tic disorders, and hypomania episodes. In Brazil, Torresan et al 25 found more posttraumatic stress disorder and tic disorders among men, whereas women presented more simple phobias, eating disorders (anorexia nervosa), as well as more impulse control disorders in general, particularly skin picking and "compulsive" shopping.…”
Section: Phenotypical Studiesmentioning
confidence: 97%
“…29 An Italian study found a higher frequency of insidious onset and chronic course among male sufferers and more episodic course among females. 19 According to Noshirvani et al, 17 similarly to schizophrenia, OCD cases with an early onset are usually more severe, reflecting the influence of cerebral lesions or constitutional aspects to which men are more vulnerable than women. Likewise, Bogetto et al 19 consider that early OCD onset is not strongly related to the impact of stressful life events but, conversely, could indicate a higher influence of biological lesions to which men are more predisposed.…”
Section: Phenotypical Studiesmentioning
confidence: 99%
See 3 more Smart Citations